Changes in isometric strength, plasma myostatin concentration and the possible relationship to weight loss periods among wrestlers - Bao, H.; Zeng, F.; Feng, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Research findings show that the sport of wrestling requires sufficient strength of both the upper and lower body musculature. In addition this activity also requires competent isometric force production capacity for various wrestling techniques. It is also known that many wrestlers undertake periods of weight loss in order to meet the criteria for a particular category. It seems plausible that strength and power production could be reduced over the course of multiple days of weight loss. Caloric restriction and physical exertion may also have a dramatic influence the endocrine function of the body. Myostatin (GDF-8) acts as a negative regulator of skeletal muscle mass, whereby animals deficient in GDF-8 show dramatic increases in muscle growth. Mice completely lacking GDF-8 gene show a 2-3 fold increase in skeletal muscle, and mutations in this gene in cattle result in the double-muscling phenotype. Methods Elite male free-style wrestlers (n=16, 22.4±2.3yr) were recruited for the study and divided into two groups: weight loss (n=8) and control (n=8). They were measured before and after a two week weight loss period to assess the effect of the low caloric diet (1200-1500kcals.day-1) and training. Body composition was quantified using the skin fold technique, testosterone and cortisol levels were determined by RIA, measurement of Urea and CK was achieved with chemistry KIT and determination of GDF-8 level was accomplished with the western blotting technique. Isometric peak torque at 60 º/s and 180 º/s was analyzed using the Biodex system and the Monark system was employed to determine Wingate test performance before and after the weight loss period. Results The results displayed that following the weight loss period, testosterone level was reduced and both cortisol level and CK activity had increased within weight loss group. There were significant reductions (7.5% and 3.0% respectively) in elbow extension peak torque at both 60º/s and 180º/s and significant elevations (6.5% and 8.9% respectively) in elbow flexion peak torque at 60º/s and 180º/s found in the weight loss group compared with the control group. In addition, following weight loss trials when compared with the control group, the knee extension peak torque of the weight loss group reduced significantly (14.5%) at 60º/s, flexion peak torque reduced (20.3%) at 180º/s, relative extension peak torque decreased (3.7%) at 180º/s and relative flexion peak torque decreased (15.3%) at 180º/s. There was no significant difference of the peak power or relative peak power in both groups before the weight loss period, however following the weight loss there were significant reductions in average power, relative average power and elevation in fatigue index within weight loss group. Discussion / Conclusions This investigation is novel within its field as it is the first study of weight category wrestlers to investigate the changes of plasma concentrations of GDF-8. The findings show that after weight loss trials, there were no significant alterations in GDF-8 concentration, but it did elevate by 7.12%. There was a trend between GDF-8 concentration and slow and fast elbow relative peak torques.